DESAIN KARAKTER UNTUK BUKU INTERAKTIF PENGENALAN ASMAUL HUSNA PADA ANAK KELAS 1 SEKOLAH DASAR - Salsabiila Millenia Nabiilah Hadaayaa; Aris Sutejo; Restu Ismoyo Aji (JURNAL IMAJINASI, 2023)
There are many phenomena such as domestic violence, sexual harassment and so on. This can happen because of the lack of fear and not fully knowing Allah SWT. therefore, the need for a solution in reducing the occurrence of this problem and one of the ways is to know Allah SWT through his good names or what is commonly called Asmaul Husna to children of early age in an interesting way so that the message of learning is communicated. Interactive books are an interesting learning media solution based on the results of analyses and interviews to the target audience. The creation of interactive books is inseparable from the design of characters in it as an important component in the preparation of illustrative narratives. The research method used is with qualitative research methods by conducting literature studies, interviews, and questionnaires. This plan aims to reduce the problems raised and attract the attention of the child in knowing and learning Asmaul Husna in everyday life